Competition's Role in Developing Psychological Strength and Outstanding Performance. Issue 3 (September 2016) - Worrell, Frank C.; Knotek, Steven E.; Plucker, Jonathan A.; Portenga, Steve; Simonton, Dean Keith; Olszewski-Kubilius, Paula; Schultz, Sheila R.; Subotnik, Rena F.
Competition, a topic closely associated with outstanding performance, continues to be a contentious topic (Bonta, 1997 ;Murayama & Elliot, 2012a, 2012b ), particularly in the realm of education and schooling (D. W. Johnson & Johnson, 1987, 2009 ). Is competition a useful or detrimental strategy for promoting outstanding performance? Does competition contribute positively to performance or should it be avoided? In this article, we took on the challenge of exploring the relationship between competition and high performance and making recommendations about how competition can be used in promoting adaptive youth development. We begin by defining competition and outstanding performance. We then discuss competition in the context of the positive psychology movement, followed by brief reviews of literature showcasing how competition is related to enhanced performance in sport, organizational settings, and academic domains. Next, we discuss competition's relationship to creativity. The article closes with a discussion of the implications of this work for practice and research. It is our hope that this work will result in increased attention to high performance psychology as an important focus for scholarship and application in a wide range of arenas, from schools and the workplace to athletic and artistic venues.